Development and testing of the BONES physical activity survey for young children. - Economos, Christina D.; Hennessy, Erin.; Sacheck, Jennifer M.; Shea, M Kyla.; Naumova, Elena N. (2016)
Background: Weight-bearing and high intensity physical activities are particularly beneficial for stimulating bone growth in children given that bone responds favorably to mechanical load. While it is important to assess the contribution and impact of weight-bearing physical activity on health outcomes, measurement tools that quantify and provide information on these activities separately from overall physical activity are limited. This study describes the development and evaluation of a pictorial physical activity survey (PAS) that measures children's participation and knowledge of high-intensity, weight-bearing ("bone smart") physical activity.; Keywords: Beat Osteoporosis: Nourish and Exercise Skeletons, metabolic equivalent time, moderate-to-vigorous physical activity, physical activity survey, vigorous physical activity, weight-bearing factor.; Springer Open.